Contribuição dos estados antianalogos as ressonâncias análogas nas reações d (\'PB POT.207\', \'PB POT.208\')p - Perez, Jose Fernando (1969)
Contribuição dos estados antianalogos as ressonâncias análogas nas reações d (\'PB POT.207\', \'PB POT.208\')p